All my friends live in my computer : trauma, tactical media, and meaning - Rajabi, Samira (Rutgers University Press, 2021)
"All My Friends Live in my Computer combines personal stories, media studies, and interdisciplinary theories to examine case studies from three unique parts of society. From illness narratives among breast cancer patients to political upheaval among Iranian-Americans, this book examines what people do when they go online after they have suffered a trauma. It offers in-depth academic analysis alongside deeply personal stories and case studies to take the reader on a journey through rapidly changing digital/social worlds. When people are traumatized, their worlds stop making sense, and All My Friends Live in my Computer explores how everyday people use social media to try and make a new world for themselves and others who are suffering. Through its attention to personal stories and application of media theory to new contexts, this book highlights how, when given the tools, people will make meaning in creative, novel, and healing ways"--